Sustainable Transformation in China’s Agricultural Sector: From Traditional Narrow Patterns to Smart Dynamic Production - John C.G. Lee; Se Tin; Juniati Gunawan (Foresight and STI Governance)
Technological transitions and the associated transformation of key sectors are radically changing the entire socioeconomic system. The agricultural sector, as one of its key links, today is intensively saturated with new technologies and management innovations. For the first time, there is an opportunity to “do things completely differently,” to restore and develop both the natural and human potential of rural areas. This makes it possible to create smart industries with their dynamic chains, complex infrastructure, large-scale digital platforms and networks, implement the concept of sustainable development, and make a transition from productivism (exclusive focus on productivity) to post-productivism (a balance between ensuring economic interests are met and guaranteeing the healthy integrity of natural diversity). This article analyzes the current state of and prospects for China’s agricultural sector from the point of view of two levels – “top-down” (state initiatives) and “bottom-up” (inputs of product manufacturers identified during a regional Foresight project, but apparently characteristic for most Chinese rural areas). The key limiting force in the development of the concepts under consideration is the too slow process of building human capital with residents living directly in rural areas and the development of related sectors in said areas.